Violence, security and the policing of Kenya's 2017 elections. Issue 2 (3rd April 2019) - Mutahi, Patrick; Ruteere, Mutuma
ABSTRACT: Considerable concern ahead of Kenya's 2017 elections that violence would mar the polls was fuelled by a history of election-related violence, a failure to address many of the underlying causes of violence, a highly polarized political environment, and opposition claims that the polls would be rigged. More specifically, there were fears that a dispute over the presidential election could lead to ethnic violence between supporters of President Uhuru Kenyatta and opposition leader Raila Odinga. There were also concerns that any protests, particularly by opposition supporters, would be met with considerable police force. Given this context, the paper addresses two issues. First, why, despite years of security reforms, limited protests were met with high levels of police force, resulting in loss of life. Second, why ethnic and gang-related violence did not become a widespread problem. The analysis highlights how the (non)occurrence of violence was encouraged by positions taken by prominent politicians, the broader legal and institutional context, and institutional cultures. Hence, the analysis moves beyond a common depiction of election-related violence in Kenya as simply ethnic and elite instigated, and seeks to provide a more nuanced account that looks at the relationship between structure, agency and different kinds of election-related violence.